1998
DOI: 10.1002/(sici)1097-0142(19980815)83:4<806::aid-cncr26>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

REAL classification of malignant lymphomas in the republic of korea

Abstract: BACKGROUND The clinicopathologic characteristics of malignant lymphomas vary according to geography. The aim of this study was to determine the clinical characteristics of malignant lymphomas and the relative frequency in the Republic of Korea of lymphomas belonging to the newly described REAL (revised European‐American lymphoma) classification categories. METHODS The Hematolymphoreticular Study Group of the Korean Society of Pathologists conducted a consensus‐based morphologic review of a nationwide collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(46 citation statements)
references
References 18 publications
5
39
1
1
Order By: Relevance
“…Based on working formula classification, Hodgkin lymphoma in this study shows a frequency like that of Korea, but it is less frequent in comparison with the US [18]. A higher incidence occurs in westernized populations including those who emigrate from lowincidence sites to the United States.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Based on working formula classification, Hodgkin lymphoma in this study shows a frequency like that of Korea, but it is less frequent in comparison with the US [18]. A higher incidence occurs in westernized populations including those who emigrate from lowincidence sites to the United States.…”
Section: Discussionmentioning
confidence: 52%
“…Our result is like the study in Korea. The median age of their patients was 52 years [18]. The reason may relate to the underlying age structure in both countries, nonetheless, it needs more population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent nationwide study of malignant lymphomas among Koreans revealed that angiocentric lymphoma accounted 8.7% of all non-Hodgkin lymphoma and 74.1% of lymphomas arising in the nasal cavity and paranasal sinuses. 16 This tumor shares immunophenotypes of T and NK cells with cCD3 expression. Be- 36 32 cause paraffin reactive antibodies against CD3 recognize the epsilon chain present in T and NK cells, confirmation of T lineage requires demonstration of TCR protein, surface CD3 expression, or a clonal TCR gene rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a recent retrospective study showed that the worst treatment outcomes were associated with skin and soft tissue involvement, especially in cases of advanced disease [2]. However, data regarding ENKTL involving the GI tract are relatively scarce [3], although the GI tract is the most common site of extranodal organ involvement in patients with non-Hodgkin lymphoma (NHL) [4,5]. A previous retrospective analysis of 581 patients with intestinal NHL reported a frequency of 3.1% of ENKTL (n = 18) and poorer prognosis than B-cell lymphomas [6].…”
Section: Introductionmentioning
confidence: 99%